2005
DOI: 10.5301/hip.2008.2
|View full text |Cite
|
Sign up to set email alerts
|

Use of re-transfusion versus vacuum drains in primary total hip replacement

Abstract: Whilst the use of re-transfusion drains in primary knee arthroplasty has gained acceptance in reducing the requirement for donor blood products postoperatively, their use in total hip arthroplasty remains uncertain. Using two groups of 32 patients, a comparison was made between re-transfusion drains and vacuum drains in primary total hip arthroplasty in one centre and the requirement for postoperative donor blood. No statistically significant difference was found between the groups in terms of blood loss (p=0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…22 Others question the clinical and economic benefit of post-operative salvage in primary THR. [23][24][25] Another concluded that although the risk of homologous blood transfusion is reduced in revision arthroplasty and in patients who have not pre-donated blood, there is no benefit in those primary THR patients able to pre-donate their blood. 26 The introduction of minimal-incision techniques has been shown to reduce intraoperative loss of blood, but the rate of post-operative transfusion is not significantly reduced when compared to conventional surgery.…”
Section: General Orthopaedicsmentioning
confidence: 99%
“…22 Others question the clinical and economic benefit of post-operative salvage in primary THR. [23][24][25] Another concluded that although the risk of homologous blood transfusion is reduced in revision arthroplasty and in patients who have not pre-donated blood, there is no benefit in those primary THR patients able to pre-donate their blood. 26 The introduction of minimal-incision techniques has been shown to reduce intraoperative loss of blood, but the rate of post-operative transfusion is not significantly reduced when compared to conventional surgery.…”
Section: General Orthopaedicsmentioning
confidence: 99%